The interaction of BDNF with estrogen in the development of hypertension and obesity, particularly during menopause - Zhang, Zhongming; He, Ziyi; Pan, Jing; Yuan, Minghui; Lang, Yini; Wei, Xiaomeng; Zhang, Chaoyun (Frontiers in Endocrinology, 2024)
The expression of BDNF in both neuronal and non-neuronal cells is influenced by various stimuli, including prenatal developmental factors and postnatal conditions such as estrogens, dietary habits, and lifestyle factors like obesity, blood pressure, and aging. Central BDNF plays a crucial role in modulating how target tissues respond to these stimuli, influencing the pathogenesis of hypertension, mitigating obesity, and protecting neurons from aging. Thus, BDNF serves as a dynamic mediator of environmental influences, reflecting an individual's unique history of exposure. Estrogens, on the other hand, regulate various processes to maintain overall physiological well-being. Through nuclear estrogen receptors (ERα, ERβ) and the membrane estrogen receptor (GPER1), estrogens modulate transcriptional processes and signaling events that regulate the expression of target genes, such as ERα, components of the renin-angiotensin system (RAS), and hormone-sensitive lipase. Estrogens are instrumental in maintaining the set point for blood pressure and energy balance.BDNF and estrogens work cooperatively to prevent obesity by favoring lipolysis, and counteractively regulate blood pressure to adapt to the environment. Estrogen deficiency leads to menopause in women with low central BDNF level. This review delves into the complex mechanisms involving BDNF and estrogen, especially in the context of hypertension and obesity, particularly among postmenopausal women. The insights gained aim to inform the development of comprehensive therapeutic strategies for these prevalent syndromes affecting approximately 68% of adults.